Intrathecal administration of AYX2 DNA decoy produces a long-term pain treatment in rat models of chronic pain by inhibiting the KLF6, KLF9, and KLF15 transcription factors. Issue 1 (August 2017) - Mamet, Julien; Klukinov, Michael; Harris, Scott; Manning, Donald C; Xie, Simon; Pascual, Conrado; Taylor, Bradley K; Donahue, Renee R; Yeomans, David C
Background: Nociception is maintained by genome-wide regulation of transcription in the dorsal root ganglia—spinal cord network. Hence, transcription factors constitute a promising class of targets for breakthrough pharmacological interventions to treat chronic pain. DNA decoys are oligonucleotides and specific inhibitors of transcription factor activities. A methodological series of in vivo–in vitro screening cycles was performed with decoy/transcription factor couples to identify targets capable of producing a robust and long-lasting inhibition of established chronic pain. Decoys were injected intrathecally and their efficacy was tested in the spared nerve injury and chronic constriction injury models of chronic pain in rats using repetitive von Frey testing. Results: Results demonstrated that a one-time administration of decoys binding to the Kruppel-like transcription factors (KLFs) 6, 9, and 15 produces a significant and weeks–month long reduction in mechanical hypersensitivity compared to controls. In the spared nerve injury model, decoy efficacy was correlated to its capacity to bind KLF15 and KLF9 at a specific ratio, while in the chronic constriction injury model, efficacy was correlated to the combined binding capacity to KLF6 and KLF9. AYX2, an 18-bp DNA decoy binding KLF6, KLF9, and KLF15, was optimized for clinical development, and it demonstrated significant efficacy in these models. Conclusions: These data highlight KLF6, KLF9, and KLF15 as transcription factors required for the maintenance of chronic pain and illustrate the potential therapeutic benefits of AYX2 for the treatment of chronic pain.